The Influence of Work Facilities and Competence on the Performance of Dapodik Operators at Public Middle Schools in Jember Regency - ‘Atho Illah Askany, Ibin; Budi Satoto, Eko; Sanosra, Abadi; Qomariah, Nurul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The complexity of school operator work is a challenge for every institution to maintain optimal data quality. However, several institutions show that the operator's work targets have not been achieved in carrying out their duties and functions. Therefore, the purpose of this study is to directly determine and analyze the influence of work facilities and competence on the performance of junior high school operators in the Jember Regency Education Office. The number of samples in this study was 94. Validity test and reliability test analysis were used as an effort to determine the validity and reliability of a construct. Hypothesis test analysis was also carried out in order to obtain direct influence results. The results of the data analysis showed that the work facility variable had a significant effect on operator performance. Meanwhile, employee competence also had a significant effect on the performance of junior high school operators in the Jember Regency Education Office. This study provides a very important contribution related to the relationship between work facilities, competence and employee performance. The results show that facilities and competence show that they can improve employee performance, which theoretically strengthens the idea that facilities and competence can improve performance.